Relationship Between Hardiness and the Mental Health of Funded Chinese College Students: The Mediating Role of Social Support and the Moderating Role of an Only-Child Status - Liu, Jingxuan; Cheng, Xiaoshuang; Li, Jun (Frontiers in Psychology, 2022)
According to the hardiness model and the perspective of different treatment by parents, this study developed and validated a moderated mediation model to explore the direct effect of hardiness on the mental health of Chinese funded college students (FCSs) , the mediating role of social support, and the moderating role of only-child (OC) /non-only-child (NOC) status. A hardiness scale, mental health scale, and perceived social support scale were used to examine information on 673 Chinese FCSs. Hardiness had a significantly positive effect on the mental health of FCSs. Mediation analysis indicated that social support mediated the relationship between hardiness and the mental health of FCSs. The moderated mediation model analysis indicated that the OC/NOC status moderated the second half of the mediation model. The results suggest that the hardiness model is applicable to FCSs from China and elucidate the internal influence mechanism between hardiness and mental health. On the basis of the findings of this study, suggestions are presented in this paper for college education management.